Enzymatic Production of Lactulose by Fed-Batch and Repeated Fed-Batch Reactor - Vera-Vera, C (Elsevier Ltd, 2021)
The effects of the most significant operational variables on reactor performance of fed-batch and repeated fed-batch were evaluated in the lactulose production by enzymatic transgalactosylation. Feed flowrate in the fed stage (F) and fructose to lactose molar ratio (Fr/L) were the variables that mostly affected the values ​​of lactulose yield (YLu), lactulose productivity (πLu) and selectivity of transgalactosylation (SLu/TOS). Maximum YLu of 0.21 g lactulose per g lactose was obtained at 50% w/w inlet carbohydrates concentration (IC) of, 50 °C, Fr/L 8, F 1 mL⋅min−1, 200 IU∙gLactose-1 reactor enzyme load and pH 4.5. At these conditions the selectivity was 7.4, productivity was 0.71 gLu∙g−1∙h-1and lactose conversion was 0.66. The operation by repeated fed batch increases the efficiency of use of the biocatalysts (EB) and the accumulated productivity compared to batch and fed batch operation with the same biocatalyst. EB obtained was 4.13 gLu∙mgbiocatalyst protein−1, 10.6 times higher than in fed-batch. © 2021 Elsevier Ltd